INCOMING AND OUTGOING MAIL ARCHIVE MANAGEMENT SYSTEM AT THE EAST JAVA PROVINCIAL RESEARCH AND INNOVATION AGENCY OFFICE - Candra Sari, Dewi; Lestari, Yuni (Jurnal Inovasi Administrasi Negara Terapan, 2025)
Abstract This study aims to describe the governance system of incoming and outgoing mail archives at the Regional Research and Innovation Agency (BRIDA) Office of East Java Province. Mail archives play a crucial role in the smooth operation of administration, and thus their management must be carried out systematically from creation to disposition. According to the theory by Mulhidin and Winata in Faulziyah (2019), ideal archive management includes four elements: creation, use, maintenance, and disposition. At BRIDA East Java, the archiving system is still conducted manually without standard operating procedures (SOP), yet it still follows administrative procedures such as mail registration, classification, and document security.This study uses a qualitative approach with a descriptive method. Informants consist of 1 head of sub-division, 3 archive management staff, and 2 archive users. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, presentation, and conclusion drawing.The research results show that the archive creation process has been well implemented and organized. However, the usage stage of the archives is still suboptimal due to the absence of clear borrowing procedures. Archive maintenance is carried out, but not optimally, due to unidentified documents and poorly organized storage spaces. Archive disposition is only partially done, limited to archive relocation, without a thorough disposition process. Keywords: Archive governance, incoming mail, outgoing mail, BRIDA East Java.